Pelatihan Pembuatan Buket Sebagai Alternatif Peluang Usaha Untuk Meningkatkan Perekonomian di Desa Muara Tiku - Ira Primalasari; Vera Octalia (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2024)
The aim of this service activity is to provide knowledge to youth organizations and the community about techniques for making snack bouquets and flowers as well as fostering skills and creativity and empowering youth organizations and communities in the Muara Tiku Village area to be more productive. The service activity is carried out by providing training in making bouquets to the students. youth groups who have finished school in Muara Tiku Village, the importance of this bouquet making training can create business opportunities for the younger generation and improve the economy. Bouquet making training can not only create business opportunities, but can also increase income. Training in making attractive and beautiful bouquets with very affordable capital, so that they can be sold with maximum profit. Making attractive bouquets will increase the added value of the product which in turn supports the sustainability of the bouquet business thereby increasing better income. Keywords: Training, Craft, Bouquet